Improving forward roll learning outcomes: implementation of direct intruction model based on audio-visual media - Amalia Ulfah; Mashud (Universitas Sriwijaya, 2025)
Research Problems: The mastery of the Forward roll lies in its role in developing motor skills and student discipline; however, the low learning outcomes indicate a need for more effective learning methods and media. Research Objectives: This study aims to improve the learning outcomes of Forward roll through a direct learning model based on audiovisual media in class VII C students. Methods: The method used in this research is classroom action research, with the Kurt Lewin model (planning, action, observation, and reflection). The subjects of this study were students of class VII C with a total of 31 students. The data collection instrument is in the form of a test (multiple choice) for the Forward roll specific motion knowledge instrument with assessment indicators, namely the benefits of the Forward roll, classification of sports branches, prefix attitude, implementation attitude, final attitude and performance for the Forward roll specific motion skill instrument with indicators of prefix attitude, implementation attitude, final attitude. The overall data in the form of quantitative data is then analyzed descriptively using the percentage formula. Results: The study's results showed an increase in student learning outcomes over one cycle. In the cognitive aspect or knowledge increased by 80, 65% and in the psychomotor or skill aspect increased by 90, 32%. Conclusion: It can be concluded that the learning outcomes of the Forward roll can be improved through a direct learning model based on audio-visual media in class VII C students. The effectiveness of this model needs to be investigated in other specific movements (long jump, volleyball, floor gymnastics) as well as including the impact on student character, including courage, trust, and sportsmanship.